2015
DOI: 10.1515/ncrs-2014-0126
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of bis[μ-1-[(2-ethyl-1H-imidazol-1-yl)methyl]-1H-benzotriazole-κ2N:N′]bis[dibromido]dimercury(II), C24H26Br4Hg2N10

Abstract: C 24 H 26 Br4Hg 2 N 10 , triclinic, P (no. 2), a = 7.587(1) Å, b = 9.801(1) Å, c = 11.037(2) Å, α = 78.81(1)°, β = 86.41(1)°, γ = 75.97(1)°, V = 781.0 CCDC no.: 1267/4124 Source of materialThe ligand 1-[(2-ethyl-1H-imidazol-1-yl)methyl]-1H-benzotriazole (0.04 mmol, 0.0096 g) in methanol (6 mL) was added dropwise to a methanol solution (6 mL) of HgBr 2 (0.04 mmol, 0.0144 g) in methanol. The resulting solution was allowed to stand at room temperature. After three weeks colourless crystals were obtained. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…polymeric, bridging either through the halide (Zhang et al, 2015;Li et al, 2007;Shen et al, 2005) or through alternative N atoms from the benzimidazole moieties (Xiao et al, 2009(Xiao et al, , 2011Huang et al, 2006;Li et al, 2007Li et al, , 2012aDey et al, 2013;Du et al, 2011;Chen et al, 2013;Su et al, 2003;Xu et al, 2011), or discrete molecules, i.e. non-polymeric (Xiao et al, 2011;Wu et al, 2009;Zhao et al, 2012;Lou et al, 2012;Zhu et al, 2009;Carballo et al, 1993;Yan et al, 2012;Hu et al, 2012Hu et al, , 2015Ding et al, 2012;Matthews et al, 1998;Manjunatha et al, 2011;Wang et al, 2007Wang et al, , 2009Wang et al, , 2012Wang et al, , 2015Chen et al, 2014;Su et al, 2003;Quiroz-Castro et al, 2000;Yang & Luo, 2012;He et al, 2012;Bouchouit et al, 2015).…”
Section: Chemical Contextmentioning
confidence: 99%
“…polymeric, bridging either through the halide (Zhang et al, 2015;Li et al, 2007;Shen et al, 2005) or through alternative N atoms from the benzimidazole moieties (Xiao et al, 2009(Xiao et al, , 2011Huang et al, 2006;Li et al, 2007Li et al, , 2012aDey et al, 2013;Du et al, 2011;Chen et al, 2013;Su et al, 2003;Xu et al, 2011), or discrete molecules, i.e. non-polymeric (Xiao et al, 2011;Wu et al, 2009;Zhao et al, 2012;Lou et al, 2012;Zhu et al, 2009;Carballo et al, 1993;Yan et al, 2012;Hu et al, 2012Hu et al, , 2015Ding et al, 2012;Matthews et al, 1998;Manjunatha et al, 2011;Wang et al, 2007Wang et al, , 2009Wang et al, , 2012Wang et al, , 2015Chen et al, 2014;Su et al, 2003;Quiroz-Castro et al, 2000;Yang & Luo, 2012;He et al, 2012;Bouchouit et al, 2015).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Many symmetric imidazole and benzotriazole ligands have been applied [3,4]. However, studies involving asymmetric imidazole and benzotriazole ligands are rather rare [5,6]. …”
Section: Discussionmentioning
confidence: 99%
“…A survey of the structural investigations of mercury halide complexes with benzimidazole derivatives has shown that they come in two main types; polymeric, bridging either through the halide (Zhang et al, 2015;Li et al, 2007;Shen et al, 2005) or through alternative N atoms from the benzimidazole moieties (Xiao et al, , 2011Huang et al, 2006;Li et al, 2007Li et al, , 2012aDey et al, 2013;Du et al, 2011;Chen et al, 2013;Su et al, 2003;Xu et al, 2011), or discrete molecules, i.e. nonpolymeric (Xiao et al, 2011;Wu et al, 2009;Zhao et al ., 1998;Manjunatha et al, 2011;Wang et al, 2007Wang et al, , 2009Wang et al, , 2012Wang et al, , 2015Chen et al, 2014;Su et al, 2003;Quiroz-Castro et al, 2000;Yang & Luo, 2012;He et al, 2012;Bouchouit et al, 2015).…”
Section: Database Surveymentioning
confidence: 99%